Usaha Mikro Kecil Menengah (UMKM) di Tengah Perubahan Global: Membangun Bisnis Online Menghadapi Kompetitor - Utami, Carolina Santi Muji; Setiawati, Nur Aini; Maryuni, Yuni (Perkumpulan Program Studi Sejarah Se-Indonesia, 2023)
The development of information technology in the 21st century is very rapid, and is experiencing very dynamic changes. Business actors in various business fields are required to be sensitive to any changes that occur. Business competition in various fields is increasing. Mastery, use and technological innovation in the 21st century will greatly affect its ability to face competitors and compete. The research problem is how the strategy of micro, small and medium enterprises utilizes e-commerce as a place for business development. The purpose of this study is to get an explanation of the strategy to face competitors and gain competitive advantage. Qualitative descriptive method is carried out by observation techniques in the form of observations and interviews. Literature study is used as a support for vacancies in the field. The analysis used is interactive descriptive analysis. The findings get an explanation of the role of Marketplace and social media as a place for producers and consumers to meet, Social media as part of the MSME strategic activities to expand networks, and reach consumers.